Social and cultural peculiarities of french lexis in the administrative and law area and criteria of its usage by communicants - Lypska, І. І.; Липська, І. І.; Липская, И. И.; Glynska, О. M.; Глинська, О. М.; Глинская, О. М. (Одеса : Гельветика, 2015)
The article is devoted to social and cultural features of the •vocabulary in the administrative study and law area. Specific features of the vocabulary of administrative and law area are provided by pragmatic approaches to the act of intercourse and based on expansion of lexical knowledge in a givenfield of communication.
Lypska I. I., Glynska О. M. Social and cultural peculiarities of french lexis in the administrative and law area and criteria of its usage by communicants / I. I. Lypska, O. M. Glynska // Одеський лінгвістичний вісник. – 2015. – Вип. 5. – Т. 2 – С. 184-187.
Keywords: administrative and law area; communicants; lexical units; socio-cultural competence; terminological blocks; адміністративно-правова сфера; комуніканти; лексичні одиниці; соціокультурна компетенція; термінологічні блоки; административно-правовая сфера; коммуниканты; лексические единицы; социокультурная компетенция; терминологические блоки